Peran prostaglandin pada pergerakan gigi ortodontik - Patricia Iskandar; Nia Ayu Ismaniati (DiscoverSys Inc., 2010)
Orthodontic tooth movement is a complex process, in which cellular and chemicalchanges occur. When a force is applied onto a tooth, it causes tissue injury,compression of periodontal ligament and bone deformation. These procedures lead tofollowed by certain biochemical reactions at cellular level which results in boneremodeling. Thus a process of signal transduction occurs. In this process, somemessengers are released, including prostaglandin. Prostaglandin is an arachidonicacid metabolite, released when cell membrane is deformed. Prostaglandin,particularly PGE, play a role in bone metabolism and orthodontic tooth movement.Prostaglandin will stimulate the release of second messengers, i.e. cAMP and calciumintracellular. These second messengers will activate osteoclasts. Prostaglandin willalso induce RANKL (receptor activator of nuclear factor ÎºÎ² ligand) to initiateosteoclasts differentiation. Some researchers proved that application of prostaglandinin orthodontic treatment can accelerate tooth movement.